The influence of temperature seasonality on elevational range size across latitude: a test using Liolaemus lizards - Sheldon, Kimberly S. (2015)
Aim Identifying factors that limit species distributions is a fundamental question in ecology with implications for understanding global biodiversity patterns and species responses to environmental change. Theory suggests that temperature seasonality may affect range size. Species at higher latitudes and elevations experience greater temperature variation, which should lead to broader thermal tolerances and elevational ranges. Research suggests that realized seasonality, or the seasonality species experience when active, may be a better predictor of distributions than annual seasonality. We tested the seasonality hypothesis by examining relationships between environmental factors and elevational range. Location Argentina. Methods We gathered data on ecology and thermal physiology for 33 Liolaemus lizards (Liolaemidae) and analysed data in phylogenetic comparative analyses using mitochondrial DNA sequences. We used 1000 tree structures and ran phylogenetic generalized least squares analyses on all 33 species and on 23 species in the boulengeri clade to determine if the elevational range of lizards shows a positive relationship with annual and realized seasonality, thermal tolerance, latitude and elevational midpoint of the species distribution. Results Latitude and elevational midpoint were good predictors of elevational range in all models. Annual seasonality was a good predictor of elevational range in models containing 33 species. Variation in phylogenetic tree structure led to differences in the best-fit statistical models. Thermal tolerance and realized seasonality were not good indicators of elevational range. Main conclusions Our findings support some, but not all, of the predictions of the seasonality hypothesis. Species at higher latitudes and elevations have larger elevational ranges, and annual seasonality is partly responsible for this increase. Yet, adult thermal tolerance shows no relationship with elevational range, suggesting that distributions may depend on the physiology of other Liolaemus life stages. Differences in phylogenetic tree structure and the number of species included in analyses can lead to different conclusions regarding the seasonality hypothesis.